Deep-sea sponge aggregations (Pheronema carpenteri) in the Porcupine Seabight (NE Atlantic) potentially degraded by demersal fishing. (April 2020) - Vieira, Rui P.; Bett, Brian J.; Jones, Daniel O.B.; Durden, Jennifer M.; Morris, Kirsty J.; Cunha, Marina R.; Trueman, Clive N.; Ruhl, Henry A.
Graphical abstract: Highlights: Deep-sea sponge aggregations identified in the 1980s were resurveyed in 2011. Sponge ( Pheronema carpenteri ) standing stocks had declined by an order of magnitude. Seafloor trawl marks were observed in the sponge grounds. Vessel monitoring data indicated commercial bottom trawling effort in the area. Without protection this deep-sea habitat, and its species, may continue to decline. Abstract: Deep-sea sponge aggregations are widely recognised as features of conservation interest and vulnerable marine ecosystems that may particularly require protection from the impact of commercial bottom trawl fishing. In 2011 we revisited deep-sea sponge aggregations in the Porcupine Seabight (NE Atlantic, c. 1200 m water depth) originally described by Rice et al. (1990, Prog. Oceanogr. 24 : 179–196) from surveys in 1983/4. Using an off-bottom towed camera system, broadly comparable to the bottom-towed system originally employed, we resurveyed four key transects detailed in that publication. In the intervening years, there has been a substantial increase in deep-water fishing activity; our primary objectives were therefore to establish the continued presence of Pheronema carpenteri (Hexactinellida, Pheronematidae), the current status of the sponge population, and whether there was any evidence of bottom trawl fishing impact on the sponges and their associated fauna. We noted a very substantial reduction in the standing stock of sponges: in Rice et al.'s (loc. cit.) peak abundance depth range (1210–1250 m) numerical density declined from 1.09 to 0.03 ind m −2, and biomass density from 246 to 4 gwwt m −2, between the surveys. Our assessment of available vessel monitoring data suggested that commercial bottom trawling had been occurring in the area, with some indication of focussed effort in the sponge's bathymetric range. We also recorded the presence of multiple apparent seafloor trawl marks on two of the transects. Despite the potential disturbance, the presence of sponge aggregations continued to exert a statistically significant positive influence on the diversity of the local megafaunal assemblage. Similarly, faunal composition also exhibited a statistically significant trend with P. carpenteri numerical density. Megafaunal numerical density, particularly that of ascidians, appeared to be enhanced in the core of Rice et al.'s (loc. cit.) peak abundance depth range, potentially reflecting the residual effect of sponge spicule mats. Our observations were suggestive of a substantive impact by bottom trawl fishing; however, a definitive assessment of cause and effect was not possible, being hampered by a lack of temporal studies in the intervening period. Other causes and interpretations were plausible and suggested the need for: (i) a precautionary approach to management, (ii) an improved understanding of sponge natural history, and (iii) temporal monitoring (e.g. seafloor sponge habitat cover).